Ici, c’est Noël tous les jours : nostalgie de l’âge d’or et recherche du travail vivant dans le pays de Bitche - Arnaud Kaba (EchoGéo)
In the deindustrialized glass-working region of the Vosges du Nord in the Pays de Bitche, Meisenthal, a village nestled in a valley, has recreated its production tool through a process of patrimonialization. The Centre International d'Arts Verriers (International Center for Glassmaking Arts), a public structure for the preservation of glassmaking know-how and experimentation, has achieved success beyond its means by marketing Christmas baubles presented as metonyms of the vanished working-class culture. By examining the friction between local policies to promote know-how and resistance from below for freer, more egalitarian working conditions, the article explores the question of living work as a desire to reproduce a craft without reproducing its logic of domination.